Genome-wide Identification and Expression Analysis of Amino Acid Transporters in the Whitefly, Bemisia tabaci (Gennadius) - Xia, Jixing (Int J Biol Sci, 2017)
The whitefly (Bemisia tabaci) is a cosmopolitan and devastating pest of agricultural crops and ornamentals. B. tabaci causes extensive damage by feeding on phloem and by transmitting plant viruses. Like many other organisms, insects depend on amino acid transporters (AATs) to transport amino acids into and out of its cells. We present a genome-wide and transcriptome-wide investigation of the following two families of AATs in B. tabaci biotype B: amino acid/auxin permease (AAAP) and amino acid/polyamine/organocation (APC). A total of 14 putative APCs and 25 putative AAAPs were identified, and a 10-paralog B. tabaci-specific expansion of AAAPs was found by maximum likelihood phylogeny. Detailed gene structure information revealed that 9 members of the B. tabaci-specific AAAP family expansion closely situated on a same scaffold. Expression profiling of the B. tabaci B APC and AAAP genes as affected by stage and plant host showed diverse expression patterns. The analysis of evolutionary rates indicated that purifying selection can explain the B. tabaci-specific AAAP expansion. RNA interference (RNAi)-mediated suppression of two AAAP genes (BtAAAP15 and BtAAAP21) significantly increased the mortality of B. tabaci B adults. The results provide a foundation for future functional analysis of APC and AAAP genes in B. tabaci.